Peran dosen dan komponen penilaian dalam meningkatkan partisipasi aktif mahasiswa di kelas - Ismail Khozen; Milla Sepliana Setyowati (Jurnal Pendidikan Ekonomi (JUPE), 2025)
Low levels of active participation among Generation Z students in traditional classroom settings remain a challenge at many universities. This study aims to investigate the role of lecturers and assessment components in the Event Planning Course (Satuan Acara Perkuliahan or SAP) as driving factors for active participation among students in the Department of Fiscal Administration (DIAF), Faculty of Administrative Sciences, Universitas Indonesia (FIA UI). A quantitative approach was employed, with data collected through questionnaires completed by DIAF students. Quantitative analysis using SmartPLS revealed that Lecturer Feedback and Components of Student Active Participation in SAP significantly influence students’ active participation. In contrast, Oral Participation and Peer Support showed no significant effects. This study underscores the critical role of lecturers, particularly through constructive feedback, in enhancing active student engagement. Descriptive findings identified student motivations and perceptions regarding the ideal weight of active participation assessment, with the largest proportion (39.7%) favoring the 6–10% range. This provides practical insights into determining appropriate weighting for participation components in SAP, relevant for designing more effective pedagogical strategies to meet professional demands in the taxation field.